2006
DOI: 10.1093/ajcn/84.3.475
|View full text |Cite
|
Sign up to set email alerts
|

The underappreciated role of muscle in health and disease

Abstract: Muscle plays a central role in whole-body protein metabolism by serving as the principal reservoir for amino acids to maintain protein synthesis in vital tissues and organs in the absence of amino acid absorption from the gut and by providing hepatic gluconeogenic precursors. Furthermore, altered muscle metabolism plays a key role in the genesis, and therefore the prevention, of many common pathologic conditions and chronic diseases. Nonetheless, the maintenance of adequate muscle mass, strength, and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
980
2
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,207 publications
(1,022 citation statements)
references
References 79 publications
14
980
2
26
Order By: Relevance
“…The role of muscular fitness in the performance of exercise and activities of daily living, as well as in preventing disease has become increasingly recognized. 63,64 Data from the AVENA study show that there is an inverse association between muscular fitness, as defined by an index computed from the standardized scores of maximal handgrip strength, explosive strength and endurance strength, and a CVD risk score (an average value from the standardized triglycerides, LDLc, HDLc and glucose) in female adolescents. 54 In addition, it was reported that for a given Fitness as a health marker in young people FB Ortega et al cardiorespiratory fitness level, an increased level of muscular fitness was associated with a lower CVD risk score (Figure 4).…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 99%
“…The role of muscular fitness in the performance of exercise and activities of daily living, as well as in preventing disease has become increasingly recognized. 63,64 Data from the AVENA study show that there is an inverse association between muscular fitness, as defined by an index computed from the standardized scores of maximal handgrip strength, explosive strength and endurance strength, and a CVD risk score (an average value from the standardized triglycerides, LDLc, HDLc and glucose) in female adolescents. 54 In addition, it was reported that for a given Fitness as a health marker in young people FB Ortega et al cardiorespiratory fitness level, an increased level of muscular fitness was associated with a lower CVD risk score (Figure 4).…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 99%
“…9,10 Resistance exercise training (for example, weightlifting) increases muscle strength and is recommended by major health organisations for improving public health. [11][12][13] In the case of pregnant women, light resistance exercise training might be easier and better tolerated than aerobic training, owing to lower cardiovascular stress and caloric expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of disease conditions often adversely affect muscle phenotype and lead to debilitating muscle wasting or atrophy. For instance, in human obesity, triglyceride accumulation in muscle (intramuscular fat) appears to be related to the development of insulin resistance and type 2 diabetes (Morio et al, 2001;Kelley et al, 2002;Wolfe, 2006). Hence, knowledge of the molecular events that affect muscle phenotype is of fundamental, agricultural, welfare and biomedical importance.…”
Section: Introductionmentioning
confidence: 99%